The Effect of Education on Quality of Life of Breast Cancer Patients With Family Assistance and Treatment Compliance As A Mediation Variable - Rolianna Harianja; Kemala Rita Wahidi; Rina Mutiara (Jurnal Health Sains, 2022)
Breast cancer is the most common type of cancer compared to other types of cancer. Breast cancer can have a psychological impact from the early diagnosis. In addition, the side effects of cancer modality therapy can also affect the psychology of patients and families. The purpose of this study was to analyze the effect of providing education on the quality of life of breast cancer patients with family assistance and medication adherence as mediating variables at the "Dharmais" Cancer Hospital. Quality of life is a subjective measure that describes happiness and freedom for an individual and how good or bad a person is. Health education is an important tool for fostering patient empowerment and encouraging their contribution to disease control. Family companion is a form of interpersonal relationship that protects a person from the effects of bad stress. Obedience comes from the root word obedient which means to obey, like to obey orders. Types of correlational research. The population is 1,174 and the sample is 291, using purposive sampling technique and proportional random sampling. Validity test using Pearson product moment. Reliability test using Cronbach alpha. Data collection techniques using questionnaires and statistical analysis of simple and multiple linear regression. The results showed that the average value of providing education, family assistance, medication adherence and quality of life was high. There was an effect of providing education (p=0.000), family assistance (p=0.001) and medication adherence (p=0.000) on the quality of life. The conclusion shows that there is the provision of education, family assistance and medication adherence to the quality of life. So it is suggested that the hospital can pay more attention to improving the quality of life such as doing health promotion.